Effect of silica on the mechanical properties of palm kernel shell based automotive brake pad - Olayide R. Adetunji; Ayodele M. Adedayo; Salami O. Ismailia; Olawale U. Dairo; Iliyas K. Okediran; Olanrewaju M. Adesusi (Mechanical Engineering for Society and Industry, 2022)
This research investigated the role of silica on palm kernel shell (PKS) as friction lining materials in automotive brake pad production. The friction materials were crushed, milled and sieved into four different particle sizes of 100, 150, 200 and 350 µm. The formulations weight percentages employed included Resin (20%), steel slag (15%) and carbon black (5%) while palm kernel shell and silica were varied for each particle size. Individual formulation was mixed for about 10 minutes until formation of homogeneous mixture.  Homogeneous formulation A, B, C and D respectively, was compacted into mould and later sintered at 150 oC for 10 minutes in electric furnace and subsequently treated to enhance quality. Produced samples were characterized and evaluated for surface hardness (SH), compressive strength (CS), flame resistance (FR), oil absorption (OA), water absorption (WA) and wear rate (WR). The particles were also characterized using Scanning Electron Microscope. The results revealed that sample D had highest SH and CS values of 105.5 Brinell hardness number (BHN) and 115.2 N/mm2 respectively with decreasing values as particle size increases. FR decreased from samples A to D, and also decreased as particle size increased. Deductively, Sample B with the sieved grade of 100 µm was the best with SH as 99.14 BHN, CS as 105.6 N/mm2, WR as 4.15%, FR as 38.98%, and WA rate as 4.26% and CF as 0.45 and OA rate as 0.381%. Conclusively, this research developed a high quality eco-friendly PKS particle composite for the production of brake pad.